Penerapan Metode Profile Matching pada Pemilihan Guru Terbaik SMK Madani - S, Susliansyah; Wijayanti, Annisa Dwi; Sumarno, Heny; Priyono, Hendro; Maulida, Linda (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2020)
Depok Madani Vocational School is a Vocational High School consisting of 2 majors namely Light Vehicle Engineering (TKR) and Computer and Network Engineering (TKJ) with 20 teachers as instructors from class X to class XII. The selection of the best teachers is done once a month to motivate the teacher in conducting teaching and learning activities. Schools in making decisions are often influenced by subjectivity and are done manually. Resulting in social jealousy among teachers and inaccurate decision results. Therefore, in assessing the best teachers a decision support system is needed in order to obtain accurate results. Decision Support System methods used in this study is Profile Matching. The method determines the value of weights on each criterion, which is to be present on time, responsibility, dress neatly and politely, participate and contribute, be active and productive, and help fellow teachers, which is followed by a ranking process. The result of the comparison of the two methods above is to produce the same chosen alternative, so that both methods can be applied to help the school's decision making.